Analisis Kemampuan Pemecahan Masalah Matematika pada Materi Pola Bilangan Ditinjau dari Gaya Kognitif Reflektif-Impulsif - Nurul Indah; Sudi Prayitno; Amrullah Amrullah; Baidowi Baidowi (Griya Journal of Mathematics Education and Application, 2021)
This study aimed to describe the mathematical problem solving ability of class VIII MTsN 1 Mataram at academic year 2019/2020 in solving numbers pattern problems based on reflective and impulsive cognitive styles. This type of research was quantitative descriptive research. The subjects in this study were students of class VIII-6 MTsN 1 Mataram at academic year 2019/2020. Data retrieval were done by using the cognitive test and the test results of problem solving. Based on the results of the study, it was found that the number of reflective students were 14 students (63,6%) who were distributed into 5 students (22,7%) with high ability, 7 students (31,8%) with moderate ability, and 2 student (9,1%) with low ability. While the number of impulsive students were 8 students who distributed into 5 students (22,7%) with medium ability and 3 students (13,6%) with low ability. Those results showed that there were differences in problem solving abilities between students who had reflective and impulsive cognitive styles. Reflective students in solving problems had been able to meet all the indicators at the problem solving stage according to Polya namely understanding the problem, thinking about the plan, carrying out the plan, and looking back. While impulsive students in solving problems had been able to fulfill the indicators thinking about plans and implementing plans. Impulsive students tend to skip the stages of understanding a problem and looking back.